2015
DOI: 10.1159/000380819
|View full text |Cite
|
Sign up to set email alerts
|

Technical Difficulties Due to Poor Acoustic Insonation during Transcranial Doppler Recordings in Amerindians and Individuals of European Origin. A Comparative Study

Abstract: Background: There is no information on transcranial Doppler (TCD) failures due to poor insonation among native inhabitants of Latin America. Methods: Seventy Ecuadorian natives and 70 age- and sex-matched individuals of European origin underwent TCD. The same investigators performed all exams using the same equipment and protocol. Using the McNemar's test for correlated proportions, we compared TCD failures related to poor insonation across ethnic groups. Results: Out of 140 participants, 56 (40%) had one or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
1
5
0
1
Order By: Relevance
“…This high number of failures was not related to external factors, because the same operators (using the same equipment and protocol) previously found a three times greater prevalence of poor insonation through temporal windows in the same population of Amerindians than in a group of age-and sex-matched individuals of European ancestry. 9 In the present study, we found a negative impact of both temporal bone thickness and heterogeneous texture on the quality of insonation. For every millimeter of increase in thickness, subjects were 2.9 times more likely to have a suboptimal/absent window.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This high number of failures was not related to external factors, because the same operators (using the same equipment and protocol) previously found a three times greater prevalence of poor insonation through temporal windows in the same population of Amerindians than in a group of age-and sex-matched individuals of European ancestry. 9 In the present study, we found a negative impact of both temporal bone thickness and heterogeneous texture on the quality of insonation. For every millimeter of increase in thickness, subjects were 2.9 times more likely to have a suboptimal/absent window.…”
Section: Discussionsupporting
confidence: 54%
“…9 In the present study, we evaluated CT findings in the same population of Amerindians to assess whether anatomic characteristics of the temporal bones accounted for the high prevalence of poor insonation.…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen of the 38 persons had absent transtemporal windows precluding insonation of both MCAs and therefore were excluded. (These high rates of absent windows were related to increased thickness and heterogeneity of temporal squama in our population of Amerindians [ 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Transcranial Doppler is a non-invasive screening method, but failures related to poor insonation through transtemporal windows limit its value in non-White populations (Nader, Andrade, Espinosa, Zambrano, & Del Brutto, 2015). Therefore, MRA appears to be the best option to assess the burden of IAS at the population level.…”
Section: Discussionmentioning
confidence: 99%